African Universities: The Way Forward - Saint, William S. (World Bank, Washington, DC, 2012)
This study explores what can be done to overcome the current crisis of quality, relevance and finance in African universities. It catalogues the accomplishments of African universities, identifies current problems, and signals likely solutions. It analyzes pertinent experience in seven key areas where changes are needed: university - state relations, financial diversification, management, governance, relevance, quality preservation, and managing the social demand for higher education. The report also suggests how a process of higher education reform can be initiated, and outlines complementary roles for government, universities and donors in the process.